MARKETING COMMUNICATION AS A FORM OF MSME DIGITAL LITERACY IN SUMEDANG REGENCY - Instianti Elyana; Fera Nelfianti; Nurzalinar Joesah; Rini Martiwi; Eulin Karlina (SEAN Institute, 2023)
The government is currently stepping up its support for the digital literacy movement in the hopes that its citizens will become not just tech-savvy but also digitally literate and able to exercise responsible behavior when using digital tools. Micro, Small, and Medium-Sized Businesses (MSMEs) in the Sumedang area are among the primary audiences for this initiative. To help micro, small, and medium-sized enterprises (MSMEs) compete on a larger scale and expand their customer base, marketing communications are being digitized. Therefore, the goal of this research is to examine MSMEs' use of digital marketing communications as a form of digital literacy. To better understand the phenomenon under investigation, this study employs a qualitative strategy and descriptive methods of analysis. Based on the findings of this research, the MSME Digital Literacy Development is implemented through the utilization of social media due to its low cost, high efficiency, and high effectiveness. Constructing content, databases, and promotional materials contributes to the growth of digital literacy. The use of social media for marketing purposes has the potential to expand the target audience beyond what could be attained through traditional channels of communication..